SIFAT PELENGKUNGAN KAYU TUSAM (Pinus Mekusii Jungh et de Vries) DENGAN DUA MACAM PERLAKUAN AWAL - Achmad Supriadi; Osly Rachman (Jurnal Penelitian Hasil Hutan, 2002)
The investigation on the bending characteristics of wood conducted in Indonesia was still very limited. In contrast, the use of bent wood in the country has intensively increase particularly in furniture industry. The preparation of such bent wood at present still dominated by sawing and planing, thereby resulting in enormous woody wastes. Besides, the strength of the corresponding wood and the beauty of its orienting fiber grains are decreasing sharply.The experiment on the bending of tusam wood taken from either its tapped or untapped portion of trees has been conducted. Tusam wood was bent with the following pretreatments : boiling the wood in the hot water al 100°C, and immersing it in urea solution. Wood bending was also prepared without such pretreatments (as control). The bending was performed at five various radiuses, i.e 80 cm; 56 cm; 45 cm; 25 cm and 15 cm. The evaluation of bending value used an ordinal scale beginning from 1 to 5 were respectively for the biggest to the smallest radius. The results of bending experiment turned out to be the best for the one with the boiling pretreatment prior to bending, and the values were consecutively 2,65; 2,28 and 1,58. The critical events occurred at 15 cm radius for the bent wood with the boiling treatment, and at 25 cm for the ones with urea immersion as well as control. The bending radius significantly effected the bending results, while the tapping and fiber grain orientation did not cause a pronounced effect.The deformation setting in the radius resulting from the bending ranged from 1,93 to 4, 13 percent. The was a trend that the longer the boiling duration, the lower the changes in the bending radius.